Introduction to the Wasteology and the Evaluation of Municipal Solid Waste Management System in Fayoum Governorate (The International Journal for Scientific Research, 2023)
In this section, we will discuss how the creation of a waste science, it will be including the classification of waste clarification some of important Definitions. The scientific basis for waste management plus the current situation of waste management in Fayoum governance (infrastructure, equipment, workers) As an example of Egypt's existing waste management problem and try to find solutions. In addition, it sheds light on some Important applications to benefit from plastic waste to produce fuel.In recent years the burdens that waste puts on the environment have been widely publicised. To address the earth's dwindling resources and the growing mountains of waste many countries have introduced statutory waste minimization and recovery targets. The general public is generally more concerned with the effects that waste has on the environment. Whereas waste managers and planners need to consider the financial costs of collection, processing, and disposal.
Keywords: Waste management; waste science; Wasteology; solid waste; Municipal Solid Waste Management